Comparison of EEG-EMG time delays calculated by phase estimates and inverse FFT - Mat Safri, Norlaili; Murayama, Nobuki (Faculty of Electrical Engineering, 2007)

(untitled)
Currently, many studies have focused on the magnitude of coherence with less emphasis on the time delay, or have mostly used only one method to establish the temporal relationship between the sensorimotor cortex and the peripheral muscles. Here, the time delays using inverse Fast Fourier transformation (IFFT), least squares regression analysis (LSR), weighted least squares regression analysis (WLSR), maximum coherence (MAX-COH) and mean of significant coherences (MEAN-COH) methods in the same subjects are compared to clarify the best method(s) for electroencephalography (EEG)- electromyography (EMG) temporal analysis. EEG activity and surface EMG activity from the first dorsal interosseous (FDI) muscle of the right hand were recorded in eight normal subjects during a weak contraction task. The current source density (CSD) reference method was estimated and used in the phase and temporal analysis. For the EEG and EMG time delay in the same subjects, MAX-COH, MEAN-COH and LSR methods are found to produce time delays that were nearer to those using transcranial stimulation compared to IFFT and WLSR methods. Therefore, the former three are more suitable compare to the latter two methods in the study of time delay between the EEG and EMG signals.